Computational Screening of Phytochemicals in Eupatorium adenophorum Extracts for Modulating Blood Coagulation: A Pharmacoinformatics Study - Dwivedi, Sushmita; Baunthiyal, Mamta (Letters in Organic Chemistry, 2025)
Wound healing is a natural phenomenon that allows tissue to repair itself after any injury. To minimize any complexity associated with wounds, they are managed with medications. Nowadays, there is growing interest in alternative sources of medication. Scientists are contemplating finding more potential in plant compounds that are promising drug targets in blood coagulation, inflammation, and wound healing research. Although there are well-established pharmaceutical products on the market for blood clotting, identifying the plant-based lead compound is challenging in hemostats and wound care. The phenomenon by which these plant compounds trigger the healing mechanism is still unknown. The current investigation aims to screen the bioactive compounds in Eupatorium adenophorum that are responsible for hemostasis activity. Gas chromatography Mass spectrometry (GC-MS) was used to perform chemical profiling of E. adenophorum’s leaf extracts in different solvents. Molecular docking was performed by using AutoDock Vina to screen the identified bioactive molecules against twenty-one target proteins found in the blood coagulation pathway. To confirm the overall structural stability of protein-ligand interactions, 100 ns molecular dynamics simulations were performed with only the A1 domain of the Von Willebrand Factor (1 AUQ), calculating RMSD (Root mean square deviation), C-alpha fluctuations, and RMSF (Root mean square fluctuations) values. Furthermore, binding energies were validated using Mechanics Poisson Boltzmann (MMPBSA) software. These ligands can be used as potential blood coagulants and wound healers after extensive in vivo investigations to assess their potential toxicological activities.
Keywords: GC-MS